Comparison of Pure and Mixed-Type Clear Cell Carcinoma of the Ovary: A Clinicopathological Analysis of 341 Chinese Patients. Issue 9 (1st November 2014) - Ye, Shuang; You, Yan; Yang, Jiaxin; Cao, Dongyan; Bai, Huimin; Huang, Huifang; Wu, Ming; Chen, Jie; Lang, Jinghe; Shen, Keng
Abstract : Objective: This study aimed to analyze the clinicopathological features of pure and mixed-type ovarian clear cell carcinoma (CCC) in Chinese patients. Methods: Patients with ovarian CCC treated in our institution between 1982 and 2012 were identified by reviewing the database and medical charts. Patients were assigned into 2 groups based on histology (pure or mixed). Comparison of clinicopathological parameters was performed to determine the similarities and/or differences between pure and mixed CCC. Kaplan-Meier model was used in survival analysis. Results: Of 341 patients with ovarian CCC, 46 (13.5%) mixed tumors were identified, and the most common combination was clear cell/endometrioid, accounting for 56.5%. Patients with mixed-type CCC tended to have higher level of serum cancer antigen 125 ( P = 0.023) and advanced tumor stage ( P = 0.001). No difference was observed in other features including age, tumor size, residual disease, lymph node metastasis, and coexisting endometriosis. Tumor recurrence occurred in 47.8% and 58.1% in patients with pure and mixed histology, respectively ( P = 0.209). Two groups had comparable platinum-sensitive disease (42.1% in pure and 44.0% in mixed type, P = 0.860). Patients with pure CCC had an improved median survival (105 vs 56 months), although statistical significance was not achieved. Histology subclassification of mixed tumor revealed that patients with clear cell/endometrioid histology had better survival outcome than those with clear cell/serous type (median survival, 140 vs 43 months, P = 0.004; median progression-free survival, 49 vs 12 months, P = 0.001). Conclusions: Patients with mixed CCC tended to have elevated serum cancer antigen 125 and advanced tumor stage. However, no significant difference was observed between the pure and mixed tumors regarding prognosis.